Falls, fractures and bone density in Parkinson's disease – a cross-sectional study. (3rd April 2017) - Tassorelli, Cristina; Berlangieri, Mariangela; Buscone, Simona; Bolla, Monica; De Icco, Roberto; Baricich, Alessio; Pacchetti, Claudio; Cisari, Carlo; Sandrini, Giorgio
Abstract : Aim : Evidence suggests that falls and associated bone fractures are more frequent in patients suffering from Parkinson's disease (PD) than in the general population. In this cross-sectional study we evaluated the clinical and biochemical characteristics that are associated to falls, fractures and bone health in a population of PD subjects. Materials and methods : Forty-two consecutive subjects suffering from idiopathic PD (mild-to-moderate severity) with/without falls in the previous year were included. They were characterized as regards functional independence, balance, fear of falling, bone density (ultrasound densitometry) and plasma levels of vitamin D. Twenty-one age- and sex-matched healthy subjects were evaluated as controls. Results : We detected a greater degree of osteoporosis in PD subjects as compared to controls, more pronounced in males than in females ( Z -score: M −3.8 ± 1.6, F −2.28 ± 0.92, p = 0.0006). A positive correlation was found between independence levels and bone density or vitamin D levels. Twenty seven patients (64%) reported falls in the previous year. These were associated to post-traumatic fractures in 16 subjects (59% of fallers). Women fell more than men (fallers: 20 F/7 M; non fallers: 4 F/11 M, χ ² test p = 0.02), although the occurrence of post-traumatic fractures among fallers did not differ between sexes (F 11/9, M 5/2, χ ² test p > 0.05). Fallers with post-traumatic fractures showed higher degrees of motor impairment. Conclusions : These findings confirm that falls and osteoporosis represent major health issues in PD, already in the middle stages of disease.